The reception of the troubadours in the Crown of Aragon - Meritxell Simó (Catalan Historical Review, 2025)
This article aims to provide an overview of the reception of Occitan troubadour poetry in the Crown of Aragon. It will examine the continuities and ruptures in the troubadour model in mediaeval Catalan literature from diverse, complementary areas of reception: the sociocultural milieu that received the poetry, the Catalan troubadours’ works, the shift from orality to writing and the Catalan manuscript tradition that has conserved the troubadour legacy.